Pengaruh Auditor Switching, Financial Distress, Komite Audit dan Kompleksitas Perusahaan Terhadap Audit Delay - Neng Hestiana; Sofie (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to examine the influence of auditor switching, financial distress, audit committee, and firm complexity on audit delay in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using a purposive sampling technique, resulting in 233 observations from unbalanced panel data. The analytical method employed is panel data regression with the assistance of EViews 12 software. The analysis results show that the audit committee has a negative effect on audit delay. In addition, auditor switching and financial distress also have a negative effect on audit delay, with financial distress demonstrating a direction of influence contrary to the initial prediction. Furthermore, firm complexity does not have a significant impact on audit delay. These findings emphasize the crucial role of internal monitoring mechanisms, particularly the audit committee, in reducing audit delay. The main implication of this study is the importance of strengthening audit committee structures and reporting capacity in complex firms to maintain stakeholder trust and promote financial reporting transparency. These findings also support agency theory, which highlights the importance of oversight in mitigating information asymmetry between management and shareholders.